Permanent Culture of Macrophages at Physiological Oxygen Attenuates the Antioxidant and Immunomodulatory Properties of Dimethyl Fumarate. Issue 5 (May 2015) - Haas, Benjamin; Chrusciel, Sandra; Fayad‐Kobeissi, Sarah; Dubois‐Randé, Jean‐Luc; Azuaje, Francisco; Boczkowski, Jorge; Motterlini, Roberto; Foresti, Roberta
<x xml:space="preserve">Abstract</x> We hypothesized that O2 tension influences the redox state and the immunomodulatory responses of inflammatory cells to dimethyl fumarate (DMF), an activator of the nuclear factor Nrf2 that controls antioxidant genes expression. This concept was investigated in macrophages permanently cultured at either physiological (5% O2) or atmospheric (20% O2) oxygen levels and then treated with DMF or challenged with lipopolysaccharide (LPS) to induce inflammation. RAW 264.7 macrophages cultured at 20% O2 exhibited a pro‐oxidant phenotype, reflected by a lower content of reduced glutathione, higher oxidized glutathione and increased production of reactive oxygen species when compared to macrophages continuously grown at 5% O2. At 20% O2, DMF induced a stronger antioxidant response compared to 5% O2 as evidenced by a higher expression of heme oxygenase‐1, NAD(P)H:quinone oxydoreductase‐1 and superoxide dismutase‐2. After challenge of macrophages with LPS, several pro‐inflammatory (iNOS, TNF‐α, MMP‐2, MMP‐9), anti‐inflammatory (arginase‐1, IL‐10) and pro‐angiogenic (VEGF‐A) mediators were evaluated in the presence or absence of DMF. All markers, with few interesting exceptions, were significantly reduced at 5% O2. This study brings new insights on the effects of O2 in the cellular adaptation to oxidative and inflammatory stimuli and highlights the importance of characterizing the effects of chemicals and drugs at physiologically relevant O2 tension. Our results demonstrate that the common practice of culturing cells at atmospheric O2 drives the endogenous cellular environment towards an oxidative stress phenotype, affecting inflammation and the expression of antioxidant pathways by exogenous modulators. J. Cell. Physiol. 230: 1128–1138, 2015. © 2014 Wiley Periodicals, Inc., A Wiley Company